Έλεγχος γονιδιακών συχνοτήτων ACAA2 στο εξώνιο 10 στα πρόβατα Χίου - Χατζηκώστα, Μύρια (Τμήμα Γεωπονικών Επιστημών, βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
The sheep and goat sector in Cyprus is 18% of livestock production with the main farmed sheep breed ''breed Chios''. Sheep either purebred or crossbred, constitute the vast majority of farmed sheep on the island and therefore the genetic improvement is great economic importance for sheep in Cyprus. So, the main purpose of breeders is to increase the Chios dairy sheep. Based on this, previous studies carried out for finding genes that affect milk and found in exon 10 of the gene ACAA2, single nucleotide polymorphism (SNP) with the T allele appears to slightly more often and be associated with high milk production. To verify the above data, this thesis research used a total 427 sheep Chios breed which originated from farms in Greece and Cyprus, from which blood was collected, followed by isolation and amplification of DNA by molecular methods such as the polymerase chain reaction (PCR) and sequencing. Subsequently tested on each farm in Cyprus and all the animals (Greece and Cyprus) if the population is in Hardy-Weinberg equilibrium and finally a comparison of genotype frequencies with statistical checking x2 between livestock Greece and Cyprus. The findings from the present study was that the genotypic frequencies did not differ between Greece and Cyprus, but confirmed that the gene frequency of the T allele is greater than that of the C-allele does not apply balance H-W, probably due to artificial selection for increased of milk production in Chios sheep.
Keywords: Sheep; The gene ACAA2